2013 International SoC Design Conference (ISOCC) 2013
DOI: 10.1109/isocc.2013.6863977
|View full text |Cite
|
Sign up to set email alerts
|

A CEA concentration measurement system using FPW biosensors and frequency-shift readout IC

Abstract: In this paper, a CEA (carcinoembryonic antigen) concentration measurement system using flexural plate wave (FPW) biosensors and a frequency-shift readout IC is presented. The proposed frequency-shift readout method employs a programmable frequency generator and a peak detecting scheme to estimate the resonant frequency. The programmable frequency generator provides a frequency scanning range from 0.9 MHz to 25 MHz according to the characteristics of the FPW biosensors. Particularly, the proposed frequency-shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The comparison between this work and the previous works [ 16 , 28 ] is shown in Table 4 , where this work has the least error. Most important of all, only two OPAs (one in the gain stage and the other in the peak detector) are used, which effectively reduce the complexity in designing high bandwidth OPAs.…”
Section: Experimental Results and Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…The comparison between this work and the previous works [ 16 , 28 ] is shown in Table 4 , where this work has the least error. Most important of all, only two OPAs (one in the gain stage and the other in the peak detector) are used, which effectively reduce the complexity in designing high bandwidth OPAs.…”
Section: Experimental Results and Analysismentioning
confidence: 83%
“…To further justify the detection architecture, this biosensor needs a readout system. Wang et al reported a high-precision readout system based on FPW sensors, where the resonant frequency shift is proportional to CEA concentration [ 16 ]. However, the input range of operational amplifier (OPA) requires at least 20 MHz bandwidth, and using too many OPAs result in higher power consumption and larger layout area.…”
Section: Introductionmentioning
confidence: 99%